2021
DOI: 10.1097/pq9.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

A QI Partnership to Decrease CT Use for Pediatric Appendicitis in the Community Hospital Setting

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In Connecticut, a quality improvement team was formed across 3 independent institutions that implemented a pediatric appendicitis clinical pathway and utilized performance improvement methods to implement change with the goal of reducing the use of computerized tomography in the work up of pediatric appendicitis. This study successfully demonstrated that engaging regional colleagues significantly decreased the use of computerized tomography in community EDs without increasing the transfer rate to a children’s hospital 9 . Children’s centers that participate in the American College of Surgeons Children’s Verification Program are encouraged to be regional leaders in children’s surgical education for all physicians, which could include medical educational activities, sharing of evidence-based clinical protocols, offering real-time clinical support and consultation, and sharing best practice from national pediatric surgical quality improvement programs with regional community hospitals (https://www.facs.org/quality-programs/accreditation-and-verification/childrens-surgery-verification/standards/standards-and-resources/).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In Connecticut, a quality improvement team was formed across 3 independent institutions that implemented a pediatric appendicitis clinical pathway and utilized performance improvement methods to implement change with the goal of reducing the use of computerized tomography in the work up of pediatric appendicitis. This study successfully demonstrated that engaging regional colleagues significantly decreased the use of computerized tomography in community EDs without increasing the transfer rate to a children’s hospital 9 . Children’s centers that participate in the American College of Surgeons Children’s Verification Program are encouraged to be regional leaders in children’s surgical education for all physicians, which could include medical educational activities, sharing of evidence-based clinical protocols, offering real-time clinical support and consultation, and sharing best practice from national pediatric surgical quality improvement programs with regional community hospitals (https://www.facs.org/quality-programs/accreditation-and-verification/childrens-surgery-verification/standards/standards-and-resources/).…”
mentioning
confidence: 85%
“…This study successfully demonstrated that engaging regional colleagues significantly decreased the use of computerized tomography in community EDs without increasing the transfer rate to a children's hospital. 9 Children's centers that participate in the American College of Surgeons Children's Verification Program are encouraged to be regional leaders in children's surgical education for all physicians, which could include medical educational activities, sharing of evidence-based clinical protocols, offering real-time clinical support and consultation, and sharing best practice from national pediatric surgical quality improvement programs with regional community hospitals (https://www.facs.org/quality-programs/accreditationand-verification/childrens-surgery-verification/standards/ standards-and-resources/). Despite decades of studying pediatric appendicitis, accurate and timely diagnosis for every patient is still elusive.…”
mentioning
confidence: 99%
“…These studies emphasize the selective use of US, resulting in reduced CT utilization. 2,[10][11][12][13] Recent studies have successfully reduced CT rates in children evaluated for suspected appendicitis with diagnostic protocols within single institutions 10,11 and in regional care systems of community hospitals. 12…”
mentioning
confidence: 99%
“…[2][3][4] There have been multiple efforts aiming to facilitate improvements in CED pediatric readiness, including the designation of a pediatric emergency care coordinator (PECC), directed pediatric education, utilization of pediatric simulations, adapting regional children's hospital clinical care guidelines, and improving equipment access. [5][6][7] With the designation of a PECC, various studies have demonstrated improvement in the quality of care for pediatric patients, pediatric education, and assessment of pediatric resources within the CEDs. 8,9 The PECC role is crucial to optimizing care for pediatric emergencies in all CEDs, which in turn requires consistent appointment by leadership and PECC empowerment by the administration and state-level programs.…”
mentioning
confidence: 99%